Actual treatment options for locally advanced and metastatic cutaneous squamous cell carcinoma - Anastasia V. Ignatova (IP Habib O.N., 2021)
Squamous cell carcinoma of the skin, or cutaneous squamous cell carcinoma (CSCC), is the second most frequent type of skin cancer, and its incidence continues to rise all over the world. Usually has a benign clinical behavior, but it can be presented as locally invasive and metastatic aggressive tumor with 2% mortality rate. Nowadays, new risk factors for have appeared, that form pharmacologically-induced CSCC after immunosuppressant drugs used for organ transplantation, or BRAF inhibitors used for melanoma. In recent years we have got a new information about the role of mutational burden, signaling pathways involved in CSCC development and new possibilities and molecules for targeted therapy. Better understanding of the immune system functioning and benefits of immunotherapy with immune checkpoint inhibitors (PD-1) for CSCC that has changed the therapeutic approach. According to recent clinical trials data, new treatment options with PD-1 inhibitors achieved a response rate of 50% for locally advanced CSCC and 47% for metastatic CSCC, including 16.1% complete remissions. This review focuses on the molecular profile, targeted therapies and immunotherapy for locally advanced and metastatic CSCC.